Smile and laughter elicited by electrical stimulation of the frontal operculum. (August 2016) - Caruana, F.; Gozzo, F.; Pelliccia, V.; Cossu, M.; Avanzini, P.
Abstract: Laughter and smile are typical expressions of mirth and fundamental means of social communication. Despite their general interest, the current knowledge about the brain regions involved in the production of these expressions is still very limited, and the principal insights come from electrical stimulation (ES) studies in patients, in which, nevertheless, laughter or smile have been elicited very rarely. Previous studies showed that laughter is evoked by the stimulation of nodes of an emotional network encompassing the anterior cingulate, the superior frontal and basal temporal cortex. A common feature of these stimulation studies is that the facial expression was always accompanied by motor awareness and often by mirth, in line with the affective functions attributed to these regions. Little is known, in contrast, on the neural basis of the voluntary motor control of this expression. The objective of this study was to investigate the effect of ES of the frontal operculum (FO), which is considered a crucial node for the linkage of the voluntary motor system for emotional expression and limbic emotional network. We report the case of ES applied to the frontal operculum (FO) in four patients with drug-resistant focal epilepsy undergoing stereo-electroencephalographic (SEEG) implantation of intracerebral electrodes. In all patients, ES applied to the FO produced laughter or smile. Interestingly, in one patient, the production of a smiling expression was also clearly accompanied by the lack of motor awareness. Since the lack of motor awareness has been previously observed only after the stimulation of the voluntary motor network, we speculate that FO is involved in the voluntary control of facial expressions, and is placed at the interface with the emotional network, gating limbic information to the motor system. Highlights: ES applied to the FO produced laughter or smile in four patients. In one patient the production of smiling was accompanied by the lack of motor awareness. ES effects were elicited from both hemispheres. FO plays as interface between voluntary and emotional networks.